IDENTIFIKASI JENIS ROTAN DI KAWASAN HUTAN ADAT DUSUN ENSIBAU DESA SEMIRAU KECAMATAN JANGKANG KABUPATEN SANGGAU - Saputra, Nobertus Geat; Idham, M; Yani, Ahmad (JURNAL HUTAN LESTARI, 2019)
Rattan in trade is generally called rattan, which is a typical tropical plant and is classified as familipalmae, including climbing plant species that require a host tree for its growth process. States that when compared with plants from other palma tribes, rattan has a variety of uniqueness, among others, the length of the stem reaches 100 m or more even though the diameter is only as big as the mother or toe, in terms of shape, rattan plants are not attractive because in part big wrapped in sharp thorny midribs. Rattan stems have extraordinary tenacity and flexibility. Because of that tenacity and flexibility, rattan sticks can be made in various forms of household furniture or other ornaments such as chairs, baskets, and so on. Especially for rattan, in West Kalimantan there are types of rattan with high economic value such as: rattan saga, branch rattan, and ring rattan. From the survey data on rattan inventory from 1990 to 2010, the distribution of rattan in West Kalimantan is generally in swamp forests and part of dryland forest. The Adat Ensibau Forest Area also has a high level of biodiversity, one of which is non-timber forest products, namely rattan. An increase in the number of people that occur around the Adat Ensibau Huatan Area is one of the causes of the emergence of pressure on the preservation of existing types of rattan, so that it will raise concerns or decrease the potential of rattan in the future.Keywords : customary forest, Ensibau hamlet, identification, rattan.